Orthogonal frequency division multiplexing (OFDM) implementation as part of a software devined radio (SDR) environment - Sonntag, Christoph (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.